PENGARUH CITRA (IMAGES), KEPUASAN KONSUMEN (CUSTOMER SATISFACTION), KEPERCAYAAN KONSUMEN (CUSTOMER TRUST) DAN LOYALITAS KONSUMEN (CUSTOMER LOYALTY) PADA PERUSAHAAN AGEN ASURANSI DI SURABAYA - Ninnasi Muttaqiin; Reizano Amri Rasyid; Candraningrat Candraningrat (Media Mahardhika, 2021)
Competition between organizations continues to increase and there is a rapid shift in the delivery of business processes. Service companies strive to improve their business processes by dealing with customers to survive and compete successfully. The literature clearly emphasizes the importance of trust and loyalty for survival in the insurance service sector. This study aims to explore the role of customer knowledge management (CKM) and satisfaction as antecedents of customer trust in the insurance agent sector. The existing causal relationships between CKM, satisfaction, trust, and loyalty were explored. The mediating role of customer trust in the knowledge-loyalty and satisfaction-loyalty relationships is also explored. Data collection was carried out through a survey with a questionnaire. The research instrument uses Structural Equation Modeling (SEM) which has been used to test the causal relationship and the suitability of the proposed model.